Amorphous ZnO based resistive random access memory. Issue 22 (12th February 2016) - Huang, Yong; Shen, Zihan; Wu, Ye; Wang, Xiaoqiu; Zhang, Shufang; Shi, Xiaoqin; Zeng, Haibo
Abstract : Amorphous zinc oxide (a-ZnO) based resistive random access memory (RRAM) Ag/a-ZnO/Pt devices were fabricated and their resistive switching characteristics investigated. Abstract : Amorphous zinc oxide (a-ZnO) based resistive random access memory (RRAM) Ag/a-ZnO/Pt devices were fabricated and their resistive switching characteristics investigated. The Ag/a-ZnO/Pt RRAMs exhibit typical bipolar resistive switching features with the resistance ratio of high to low resistance states (HRS/LRS) more than 10 7 . Detailed current–voltage I – V characteristic analysis suggests that the conduction mechanism in the low resistance state is due to the formation of metallic filaments. Schottky emission is proven to be the dominant conduction mechanism in the high resistance state which results from the Schottky contacts between the metal electrodes and ZnO. The Ag/a-ZnO/Pt devices also show excellent retention performance. These results suggest promising application potentials for Ag/a-ZnO/Pt RRAMs.